2021
DOI: 10.3390/antiox10111692
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Ultrasol Curcumin Boosts Muscle Endurance and Reduces Muscle Damage in Treadmill-Exhausted Rats

Abstract: Curcumin positively affects performance during exercise and subsequent recovery. However, curcumin has limited bioavailability unless consumed in larger doses. In the current study, we examined the impact of a new formulation of curcumin, Next-Generation Ultrasol Curcumin (NGUC), which is relatively more bioavailable than natural curcumin on exhaustion time, grip strength, muscle damage parameters, and serum and muscle proteins. A total of 28 rats were randomly grouped as control (C, non-supplemented), exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Kaempferol effectively reduced the serum MDA levels, indicating a decrease in lipid peroxidation. This finding aligns with previous research that excessive oxidative stress contributes to exercise-induced fatigue and may impair exercise performance [39]. Therefore, kaempferol possesses antioxidation capacity and positively modulates the antioxidant defense system, thereby improving exercise performance.…”
Section: Effect Of Kaempferol On Biochemical Parameters After Exercisesupporting
confidence: 91%
“…Kaempferol effectively reduced the serum MDA levels, indicating a decrease in lipid peroxidation. This finding aligns with previous research that excessive oxidative stress contributes to exercise-induced fatigue and may impair exercise performance [39]. Therefore, kaempferol possesses antioxidation capacity and positively modulates the antioxidant defense system, thereby improving exercise performance.…”
Section: Effect Of Kaempferol On Biochemical Parameters After Exercisesupporting
confidence: 91%
“…After the training period, treadmill running until exhaustion was used to measure endurance capacity. Animals were forced to run on a motorized treadmill (5/lane) at 36 m/min speed until exhausted ( Sahin et al, 2021 ). Exhaustion was defined as the inability of the rat to maintain an appropriate pace despite continuous hand prodding for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…A mild grip was applied to the tail of each rat until it released the pull rod. Peak values were recorded after five consecutive tests ( Sahin et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study indicated that NGUC reduced mTOR phosphorylation similarly to that of the PGC-1α protein level and diminished MAFbx and MuRF1 protein levels. In conclusion, curcumin promoted muscle recovery and exercise performance, attenuating muscle damage and activating anti-inflammatory, antioxidant, and muscle-mass regulatory signaling in a dose-dependent manner [ 66 ]. In another eccentric exercise model, curcumin was administered over 20 days via oral gavage at doses of 200 mg/kg bw dissolved in corn oil.…”
Section: Curcuminmentioning
confidence: 99%